Transaksi Pesanan Barang pada E-commerce Perspektif Syekh Yusuf Al-Qardawi dan UU Perlindungan Konsumen - Ahmad Muzakki (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2024)
One of the advantages or advantages of ordering goods transactions on E-commerce today is very helpful for everyone in terms of meeting all their needs. With only capital payment first then wait for the order to arrive at home. However, apart from these positive things, there are also some risks arising from order transactions using E-commerce, one of which is the incompatibility of the ordered goods. The problems in this study are (1) How are goods order transactions on E-commerce from the perspective of Sheikh Yusuf Al-Qardawi (2) How are goods order transactions on E-commerce from the perspective of the Consumer Protection Act article 1 paragraph 1 No.8 of 1999?.This study aims (1) to determine goods order transactionson E-commerce perspective of Sheikh Yusuf Al-Qardawi (2) To find outgoods order transactions on E-commerce protection law perspective consumer article 1 paragraph 1 No 8 of 19992 The research method used is to use a library research approach. In determining the source of data using primary and secondary materials, while the data collection method used is literature study or documentation. Methods of data analysis using literature study. The conclusions of this study are: (1) transactions for ordering goods on E-commerce including salam contracts which are legal if there are no elements that damage them (2) transactions for ordering goods on E-commerce from the perspective of the consumer protection law have violated the policy of the law because consumers does not accept consumer rights which have been regulated in the Consumer Protection Act Article 1 paragraph 1 No.8 of 1999 concerning consumer rights Keywords: E-commerce, Sheikh Yusuf Al-Qardawi's Perspektive, Consumer Protection Law